Nicaragua : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2012)
The paper is an elaborated report on Nicaragua's potential economic growth. The challenges and idiosyncratic shocks were immense but the policies of better education, labor contracts, and accomplishments in public investments paved the way for movement of the economy. The external competitiveness and exchange rate assessment also have an important hand. The achievements in the electricity sector and the improvement in reforming the pension system are the prominent aspects. On the whole, the Board considers this growth as a positive trial of development in the global panorama.